A PRELIMINARY STUDY ON THE UNDERSTANDING OF ISLAMIC BUSINESS ETHICS AMONG HAWKERS OF SAIMOR PATTANI, THAILAND - Farok Zakaria, (Journal of Islamic, Social, Economics and Development, 2021)
Business ethics is one of the areas of concern when one discusses about themanagement and outcome of running a business. This aspect is even important for a Moslembusiness since it is bind to the principle of Islam in making a business. Business in Islamregardless of size and type must follow suit all the principles related to business in Islam suchas no cheating in weighing, selling halal items, diligent, always tawakkal to Allah and manyother Islamic business behavior. In Islam it is considered as Fardhu Kifayah for Moslem toengage in business if it really needed by fellow Moslems. In relation to that, many Moslems inPattani have chosen entrepreneurship or doing business as their career path and the questionhere is are they really/ strictly follow the ethic of Islamic businesses in their daily businessoperations. A total of 25 small street hawkers were interviewed on what they understand andpractice with regards to Islamic business ethics. It was found that most of the hawkers viewedhalal, not cheating and wearing Moslem clothing as Islamic business ethics. Others likeworking hard and tawakkal to Allah is considered as something that as the least rememberedIslamic values that they should hang on. This paper presents the findings on how smallbusinesses at the flourishing street of Moor or popularly known as Saimoor perceive Islamicbusiness ethics and discusses some possible actions to better guide those business owners inobeying Islamic business ethics.